The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/fuce.201900235
|View full text |Cite
|
Sign up to set email alerts
|

Industrial Perspective on Hydrogen Purification, Compression, Storage, and Distribution

Abstract: Green hydrogen production by electrolysis using renewable power allows for decoupling the time and location of hydrogen production and use. Even if pipeline transport of hydrogen is most economic for large scale, transport by trailers will be present in near and mid‐term future since the construction of a hydrogen pipeline network will take a long time. Furthermore, the volume of trailer transport will increase with increasing hydrogen demand raising the question what the best hydrogen carrier is. Within this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(16 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…An in-depth insight into optimal energy system layout and conditions for economic feasibility was provided by Morgenthaler et al (2020). Syngas, as an important intermediate of the chemical industry, is neither transported nor directly sold as a final product, in contrast to H 2 (Peschel, 2020). This might be the reason that only one life cycle assessment (LCA) study was found analyzing solely the production of syngas so far (Sternberg and Bardow, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…An in-depth insight into optimal energy system layout and conditions for economic feasibility was provided by Morgenthaler et al (2020). Syngas, as an important intermediate of the chemical industry, is neither transported nor directly sold as a final product, in contrast to H 2 (Peschel, 2020). This might be the reason that only one life cycle assessment (LCA) study was found analyzing solely the production of syngas so far (Sternberg and Bardow, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many studies concern the comparison of the economical aspects of storing hydrogen in LOHC compared to compresses gas or liquefied H 2 [74,75]. Some recent studies [43,76] conclude that if the heat needed for dehydrogenation is sustainably managed (e.g., waste heat), dibenzyltoluene or toluene are systems of choice both in terms of efficiency and costs.…”
Section: Economical Studiesmentioning
confidence: 99%
“…Industrial practice specifies a deoxygenation reactor (Peschel, 2020) which catalytically combines hydrogen with oxygen to generate additional water in an exothermic reaction. In this work the inlets are fed at electrolysis temperature of 60 °C before entering the adiabatic reactor and reducing oxygen concentration to 1 ppmV, also consuming hydrogen and generating additional water vapour in line with the reaction:…”
Section: Hydrogen Purification (H 2 -Fed Cell Only)mentioning
confidence: 99%
“…Drying the hydrogen can be done in a number of ways involving condensation, temperature or pressure swing adsorption, molecular sieve adsorbents or a combination of options (Ligen et al, 2020;Peschel, 2020). Increased interest in the energy requirements of this step result from the efficiency concerns of green hydrogen production and use.…”
Section: Hydrogen Purification (H 2 -Fed Cell Only)mentioning
confidence: 99%